1982
DOI: 10.1017/s0305000900004906
|View full text |Cite
|
Sign up to set email alerts
|

Style and stability in mother conversational behaviour: a study of individual differences

Abstract: This paper explores differences in conversational style among mothers. Although previous research suggests that many aspects of mother speech to the child covary in a way which serves the underlying intention of the mother, it was unclear whether such clusters of conversational behaviour would prove useful in characterizing stylistic differences among mothers across time. An analysis of the functionally-coded speech of 11 mothers showed statistically significant variability among mothers, especially in those b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
1
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 19 publications
(53 reference statements)
5
76
1
2
Order By: Relevance
“…Parents' conversational style during toy play is often contrasted with their conversational style in other contexts (Olsen-Fulero, 1982;Yoder and Kaiser, 1989). For example, Hoff-Ginsberg (1991) contrasted the contexts of dressing, feeding, book reading, and play, finding that toy play had the highest rate of behavior directives and the lowest rate of conversationeliciting utterances from mothers.…”
Section: Focus Of Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents' conversational style during toy play is often contrasted with their conversational style in other contexts (Olsen-Fulero, 1982;Yoder and Kaiser, 1989). For example, Hoff-Ginsberg (1991) contrasted the contexts of dressing, feeding, book reading, and play, finding that toy play had the highest rate of behavior directives and the lowest rate of conversationeliciting utterances from mothers.…”
Section: Focus Of Previous Studiesmentioning
confidence: 99%
“…The kind of conversational interaction that promotes children' s participation in conversations and complexity in their expressions has been called a conversation-eliciting style of interaction (Olsen-Fulero, 1982;Yoder and Kaiser, 1989). In such a style parents stay on the child' s topic, elaborate and expand on the child' s utterances, ask questions, and encourage the child' s participation in the conversation.…”
mentioning
confidence: 99%
“…Further, the results of some observational studies are consistent with the view that mothers (and other adults) adapt their verbal and gestural communication in a manner that would facilitate lexical learning in infants. For example, when adults named objects and actions on which infants were focused, rather than those outside their focus, infants learned words rapidly (Akhtar, Dunham, & Dunham, 1991;Olsen-Fulero, 1982;Tamis-Lemonda & Bornstein, 1989). However, other studies have reported that mothers often name objects and actions outside infants' immediate attentional focus (Collis, 1977;Harris, Jones, & Grant, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a unique set of speech modifications termed Motherese (Olsen-Fulero, 1982) is well documented in the research literature (Gleitman, Newport & Gleitman, 1984;Furrow, Nelson & Benedict, 1979;Tiegerman, 1984;ContiRamsden, 1985). Mothers use Motherese when they are talking to young children, usually in their first two years of life (Owens, 1984).…”
Section: Introductionmentioning
confidence: 99%